Implementation of Living Values Education (LVE) With Islamic Integration: Building Honesty and Responsibility in Preschool Children please make an introduction that contains - Saridah, Siti; Saona, Saona (Sekolah Tinggi Agama Islam Kuningan, 2024)
Background: The integration of media and technology in early childhood education has rapidly increased, particularly after the COVID-19 pandemic. However, understanding how educators and parents experience and perceive this integration remains limited. This phenomenological study explores the lived experiences of 52 participants, including 28 early childhood teachers and 24 parents, regarding technology integration in learning environments for children aged 3-6 years. Objective: The study aims to explore the experiences of teachers and parents regarding the integration of technology in early childhood education and the challenges they face. Method: Data were collected through semi-structured interviews, focus groups, and reflective journals over a 10-month period, analyzed using van Manen’s phenomenological methodology. Findings and Implications: Findings reveal four major themes: (1) Balancing Benefits and Concerns, (2) Parent-Teacher Communication and Collaboration, (3) Digital Literacy and 21st Century Skills Development, and (4) Implementation Challenges and Support Needs. Teachers reported technology enhanced engagement and creativity, while parents expressed concerns about screen time and social development impacts. Conclusion: The study suggests that successful technology integration requires collaborative partnerships between educators and families, robust professional development, age-appropriate digital citizenship education, and policies supporting balanced, developmentally appropriate practices.